Research on Crowdfunding: Reviewing the (Very Recent) Past and Celebrating the Present. (7th February 2017) - Short, Jeremy C.; Ketchen, David J.; McKenny, Aaron F.; Allison, Thomas H.; Ireland, R. Duane
Abstract : Crowdfunding is a rapidly growing phenomenon wherein entrepreneurs seek funding for their entrepreneurial activities from a potentially large audience of interested individuals. Crowdfunding has exploded in popularity over the last decade and now accounts for tens of billions of dollars annually. But despite the importance and growth of crowdfunding, little scholarly knowledge exists about the topic. To address this gap, this special issue includes five articles that each advance knowledge about crowdfunding in important ways. We briefly review past work on crowdfunding in leading entrepreneurship and management journals. We then highlight the diverse contributions offered in the special issue articles.